(untitled) (IF-Sophia: revista eletrônica de investigações Filosófica, Científica e Tecnológica, 2016)
This paper aims at discussing how the English current status as a global language can positively influence language teaching practices. In order to do so, misconceptions about the nature of English and its role as a widely used means of communication are addressed at the beginning of the article, followed by the impact the new status has created in both native and non-native speakers. The issues regarding the teaching process itself involve the political choices teachers make, the incongruence of having a privileged accent in the classroom and how an Intercultural Approach can help build a democratic globalization when it comes to teaching and learning English. The changes concerning the concepts of foreign language and native speaker are also briefly addressed, intending to present their contributions to the process of teaching English as a global language.